Scenario Analyses for By‐Products Reuse in Integrated Steelmaking Plants by Combining Process Modeling, Simulation, and Optimization Techniques - Matino, Ismael; Branca, Teresa Annunziata; Fornai, Barbara; Colla, Valentina; Romaniello, Lea (Steel research international, 2019)
Steel industry consumes resources and produces important amounts of by‐products. Process modeling, simulation, and optimization can address field tests for maximizing by‐products reuse. The improvements of a long‐lasting research activity on slag reuse by deepening aspects, only marginally considered in the past, are presented herein. An Aspen Plus‐based model is developed to assess different basic oxygen furnace slag pretreatment configurations or involved techniques. A previously developed superstructure is upgraded, considering more slag pretreatments and qualities. A simplified Aspen Plus‐based model of mixing of the different pretreated by‐products is applied to evaluate the chemical composition of pellets in each scenario, starting from the computed mixtures. The developed tools are exploited to get a holistic view of steelmaking by‐products reuse and make multiobjective optimization studies which provide different results. For instance, the mixture to be pelletized completely changes if final product quality is (or not) considered in the optimization. Regarding the optimization combining all the considered objective functions, the best slag treatment includes a wet high‐intensity magnetic separation stage, and only some slag qualities are considered in the pellet mixture. A preliminary economic analysis confirms that an optimal combination of internal and external recoveries of by‐products can produce noteworthy revenues. A novel methodological approach is carried out to achieve high efficiency in the use of by‐products. Different new models are developed to achieve the best treatment for basic oxygen furnace slag and the best reusing route for pellet composition. The internal reuse of these pellets in the sinter mix can also be economically advantageous.